Aplicação de MALDI-TOF MS na caracterização de microalgas da família Selenastraceae (Chlorophyta) - Mello, Rodrigo Ventura de (Universidade Federal de São Carlos, 2016)
The morphological variability in the Selenastraceae family has been a barrier to a good establishment of well-defined taxonomic groups. Several studies with molecular compounds have already demonstrated its importance in the elucidation of this relation. In this scenario, the present study used a matrix-assisted laser desorption ionization timeof- flight mass-spectrometry (MALDI-TOF MS) technique as a tool to differentiation of the microalgae of this family at the species and strains levels. A group of 18 strains, belong to in 12 different species, of freshwater microalgae was selected. Cells and dissolved organic matter (DOM) were analyzed in the middle exponential growth phase. The analyzes were performed in two different mass ranges: 400 to 2,000 Da and 2,000 to 20,000 Da. Each strain that yielded unique spectra with a good resolution of peaks and reproducibility was selected for clusters analyzes. These spectra were used to make a dissimilarity analysis that showed the capability of differentiation of the strains and species. The strains of the genera Monoraphidium were not all grouped, possibly because it is a polyphyletic group. The praticity and quickness of this technique for data acquisition, allied with the low cost of the analysis, are factors that favor its application in taxonomic studies.
Keywords: Taxonomia; Microalgas verdes; Selenastraceae; Green microalgae; Taxonomy; CIENCIAS BIOLOGICAS::ECOLOGIA